Erratum: Analisis Kebutuhan Software Pengelola Hasil Tes Fisik Pencak Silat Remaja Kategori Tanding - Deny Pradana Saputro; Muhammad Riski Adi Wijaya; Muhammad Fadli Dongoran (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.842 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.